Apology strategies used by Chinese speakers in a Chinese TV series / Hai Yan - Hai, Yan (2017)
This study is an investigation of apology strategies used by Chinese speakers, it also looks at the relationship between social status and the speakers’ choice of apology strategies. Data used in this study include 57 sets of apology exchanges collected from a Chinese TV series produced in mainland China. The analytical framework used in the current study was modified based on Olshtain and Cohen (1983) and CCSARP (Cross- Cultural Speech Act Realization Project, Blum-Kulka & Olshtain, 1984). The findings revealed that out of the strategies listed in the framework, three new types of substrategies were identified in the corpus of this study, comprising expression of embarrassment, asking for another chance, and mentioning the offence committed. The most frequently used apology strategies were the IFIDs (Illocutionary Force indicating Devices), taking responsibility, and explanation. Further investigation showed that female and male speakers choose different strategies to express their apologies to female and male hearers of different social statuses. For example, female speakers preferred to apologize to higher status female hearers rather than to equal status female hearers. The findings of this study could be beneficial to Chinese learners in enhancing their communication skills in making apologies. The finding can also be used to make comparisons of apology strategies made in Chinese and other languages.